Abuse, self-harm and suicidal ideation in the UK during the COVID-19 pandemic. (October 2020) - Iob, Eleonora; Steptoe, Andrew; Fancourt, Daisy
Summary: This study explored patterns of abuse, self-harm and thoughts of suicide/self-harm in the UK during the first month of the COVID-19 pandemic using data from the COVID-19 Social Study ( n =44 775), a non-probability sample weighted to population proportions. The reported frequency of abuse, self-harm and thoughts of suicide/self-harm was higher among women, Black, Asian and minority ethnic (BAME) groups and people experiencing socioeconomic disadvantage, unemployment, disability, chronic physical illnesses, mental disorders and COVID-19 diagnosis. Psychiatric medications were the most common type of support being used, but fewer than half of those affected were accessing formal or informal support.